Cynical suspicions and Platonist pretentions : a critique of contemporary political theory - McGuire, John (Research Fellow) (Social and critical theory ;, 2018)
In Cynical Suspicions and Platonist Pretensions , John McGuire offers a critique of recent trends in contemporary political theory, specifically concerning the 'dangers' of cynicism and the contamination of public reason. In the view of many theorists and pundits, cynicism remains one of the gravest ills to befall any democratic society, injecting a virulent estrangement which leaves sufferers unable to trust elected representatives and unwilling to participate in collective action. Starting with a reconstruction of the performative and rhetorical tactics of the 'first' Cynic, Diogenes of Sinope (c. 323 BCE), John McGuire aims to demonstrate how cynicism's non-defeatist, relentlessly sceptical ethos provides an important counterweight to the self-aggrandising designs of moralists and policymakers alike.